Analisis Kemampuan Siswa Menyelesaikan Soal Matematika Berdasarkan Teori APOS Ditinjau dari Aktivitas Belajar Siswa - Lisha Surya; Yuyu Yuhana; J. Jaenudin (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This purpose of the research is to describe and analyze the student abilities to solve math problems based on APOS theory in term of the student learning activities level. The instrument of this research consist of test instruments, there are written test and a non-test instrument, there were student learning activities questionnaire and interview guidelines. The data collection technique used written test with the material of polyhedron and non-test in the form of questionnaires and semi-structured interviews. The research subjects were students of class VIII F of SMP Negeri 1 Kota Serang and the total of the samples were six students based on purposive sampling. Data analysis techniques used the data reduction, data visualization and drawing conclusions. The result of the research showed that student abilities to solve math problems based on APOS theory, that’s students who had high categorization of learning activities tended to be able to pass all stages of APOS theory, students who had moderate categorization of learning activities tended to be able to passed through all stages from the APOS theory, the students who had learning activity categories tend to able to passed through, Actions, Processes and Objects and the students who had low categorization of learning activities tend to be able to passed through only the Action and Process.